2002
DOI: 10.1186/cc1511
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The detection of endotoxemia may provide a clue to the cause of sepsis or may indicate translocation of endotoxin from the gastrointestinal tract. A reliable endotoxin activity assay (EAA) offers the potential to determine Gram-negative infections in critically ill patients. In addition, a reliable EAA may indicate the adequacy of gastrointestinal tract perfusion, as well as potentially help to predict morbidity and mortality. A recent study by Marshall and colleagues, published in the present issue of Critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…A particular difference of our work is that the EAA measurement and other laboratory data as well as blood cultures were done on identical blood samples. Therefore, the present results could be more reliable than those of previous studies, which showed differences between the results of the EAA and incidence of documented Gram-negative infections [3,8]. Similar to previous investigations, our study is limited in that the study patients had the decision whether to perform an EAA made on the basis of clinical bedside assessment of suspicion of sepsis rather than studying all ICU patients.…”
Section: Discussionsupporting
confidence: 74%
“…A particular difference of our work is that the EAA measurement and other laboratory data as well as blood cultures were done on identical blood samples. Therefore, the present results could be more reliable than those of previous studies, which showed differences between the results of the EAA and incidence of documented Gram-negative infections [3,8]. Similar to previous investigations, our study is limited in that the study patients had the decision whether to perform an EAA made on the basis of clinical bedside assessment of suspicion of sepsis rather than studying all ICU patients.…”
Section: Discussionsupporting
confidence: 74%
“…To find an ideal template for fabricating such an HRA film, the popular simple and low-cost method to prepare wrinkled elastomers was adopted. [42] In terms of the choice of ionic gel materials, as a gel electrolyte widely used in the field of energy storage, PVA/H 3 PO 4 is an excellent material for ionic gel layer due to its high ionic conductivity and good flexibility. Due to the characteristics of film formation, PVA/H 3 PO 4 can not only be used for molding to prepare the dielectric layer, but also can be used for coating and transfer silver nanowire films to prepare flexible electrodes.…”
Section: Experimental Characterization For Hra-based Iontronic Sensormentioning
confidence: 99%
“…where, ε c and t are the critical strain, releasing strain and thickness of the hard thin layer, respectively. [42] It is clear from Equations ( 4) and ( 5), the ripple wavelength and ripple amplitude are influenced obviously by releasing strain (ε) and critical strain (ε c ). Due to the fact that ε depends on the length of the prestretch while ε c belongs to the intrinsic property of the used material, the fold pattern obtained by releasing the stretched PDMS film is regulable and stable.…”
Section: Experimental Characterization For Hra-based Iontronic Sensormentioning
confidence: 99%
See 1 more Smart Citation